2020
DOI: 10.1038/s41380-020-0827-0
|View full text |Cite
|
Sign up to set email alerts
|

A reciprocal inhibition model of alternations between under-/overemotional modulatory states in patients with PTSD

Abstract: Patients with posttraumatic stress disorder (PTSD) appear to manifest two opposing tendencies in their attentional biases and symptoms. However, whether common neural mechanisms account for their opposing attentional biases and symptoms remains unknown. We here propose a model in which reciprocal inhibition between the amygdala and ventromedial prefrontal cortex (vmPFC) predicts synchronized alternations between emotional under-and overmodulatory states at the neural, behavioral, and symptom levels within the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 75 publications
3
16
0
Order By: Relevance
“…These advantages might address limitations previously discussed concerning the clarification of key patterns of neural activity underlying the whole DS 56 . Moreover, this methodological approach might sustain extensions of existing neurobiological models of dissociative‐related disorders 28,29 above and beyond the PTSD.…”
Section: Clinical Features Of Dissociation Across the Dissociative Sp...mentioning
confidence: 94%
See 1 more Smart Citation
“…These advantages might address limitations previously discussed concerning the clarification of key patterns of neural activity underlying the whole DS 56 . Moreover, this methodological approach might sustain extensions of existing neurobiological models of dissociative‐related disorders 28,29 above and beyond the PTSD.…”
Section: Clinical Features Of Dissociation Across the Dissociative Sp...mentioning
confidence: 94%
“…Furthermore, provisional considerations suggested that compartmentalization should be viewed as the key mechanism underlying somatoform dissociative symptoms among individuals with CD and SDs 12 . PTSD shows a constellation of dissociative phenomena, including positive dissociative symptoms (e.g., reexperiencing) and negative dissociative symptoms (e.g., emotional numbing) 28,29 . Referring to PTSD linked to repeated interpersonal traumatic experiences (PTSD‐IT) and DDs (e.g., dissociative identity disorder [DID]), clinical literature posits at the base of these conditions a key role of a “structural dissociation.” 30,31 This kind of structural dissociation is sustained by a complex system of dissociative symptoms including negative psychoform dissociative symptoms (e.g., amnesia and numbing), negative somatoform dissociative symptoms (e.g., anesthesia and sensory loss), positive psychoform dissociative symptoms (e.g., traumatic memories and nightmares), and positive somatoform dissociative symptoms (intrusions of sensorimotor aspects of traumatic reexperiences and pain) 31,32 …”
Section: Clinical Features Of Dissociation Across the Dissociative Sp...mentioning
confidence: 99%
“…While the aforementioned studies on functional connectivity have significantly increased our understanding of the brain as a system that obeys network-wide principles, they are mainly agnostic to temporal dynamics within the scanning sessions. This may prevent the level of precision that could at times be the most clinically relevant [45]. Differently from [16,20], where time seemed to play a negligible effect, we found that different scanning days greatly affected our estimation of brain network dynamics.…”
Section: Recent Years Have Witnessed a Growing Interest In The Identimentioning
confidence: 65%
“…In other words, a one-size-fitsall approach could be employed to build the model in its general terms, consequently allowing us to move to a personalized course of action by evaluating the model at the individual level. For instance, closed-loop fMRI neurofeedback [50,51] could significantly benefit from these models, which will allow for a more holistic approach to the dynamical properties of mental and cognitive processes, particularly from a clinical perspective [37,45,52,53].…”
Section: Recent Years Have Witnessed a Growing Interest In The Identimentioning
confidence: 99%
“…The negative weights within the left dlPFC highlight the reciprocal relation between this region and activity in the limbic system (i.e., amygdala and hippocampus). In this context, it is worth noting that there is debate about whether aberrant functional connectivity in PTSD reflects alterations in top-down regulation of the limbic system (e.g., amygdala) via the prefrontal cortex [34][35][36][37][38][39] or altered reciprocal regulation between these regions [108,109]. It is unclear whether the temporal resolution of fMRI (e.g., 1-2 seconds) is suitable for studying these dynamic and directional connections.…”
Section: Discussionmentioning
confidence: 99%